Analisis Implementasi Kebijakan Pajak Hiburan Dalam Upaya Meningkatkan Pajak Daerah Pada Masa Pandemi Covid 19 Di Kota Bekasi - Mariza Putri Darliant PS; Dwikora Harjo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The phenomenon behind this research is the significant decrease in entertainment tax revenue due to the Covid-19 pandemic. The purpose of this study is to determine the implementation of the entertainment tax policy in an effort to increase local tax revenue during the Covid -19 pandemic in Bekasi City, along with the obstacles and efforts made by Bapenda (Regional Revenue Agency) in increasing entertainment tax revenues during the Covid-19 pandemic in Bekasi City. This research is a descriptive research with a qualitative approach. The method used is qualitative data analysis method. The results of this study indicate that the implementation of the entertainment tax policy in an effort to increase local tax revenues has been going quite well. The driving factor is that the Bekasi City’s Bapenda provides relief in the administration of tax payments to taxpayers, in accordance with the Bekasi City Bapenda policy regulations.